Biodegradation of wastewater in alternating aerobic-anoxic lab scale pilot plant by Alcaligenes sp. S3 isolated from agricultural field - Geed S.R.; Prasad S.; Kureel M.K.; Singh R.S.; Rai B.N. (My University, 2025)
The isolated microbial Alcaligenes sp. S3 from the agricultural field was used for the biodegradation of synthetic wastewater containing atrazine. This study was conducted in an alternating aerobic-anoxic lab scale pilot plant. The performance of continuously operated pilot plant was evaluated in three different phases with varying atrazine concentration. The best performance of plant was observed in phase-II. The atrazine (200 mg/L) having COD value 1356 mg/L was used with varying flow rate and 90.56% COD removal was obtained at a flow rate of 300 mL/h on 122th day of operation. The effect of process parameter like pH and DO on the performance of the reactor was studied. The GC-MS analysis was investigated, and urea was found the intermediate/metabolites of atrazine biodegradation. The kinetic parameters such as half saturation rate constant (Ks) 106.80 mg/L; maximum specific growth rate (μmax) 0.208 per day and inhibition constant (Ki) 374.91 mg/L were evaluated by Andrew-Haldane model. © 2018 Elsevier Ltd